Genetic diversity of the indigenous cattle of Kenya, Uganda, Ethiopia and Tanzania using high-density SNP data - Weerasinghe, Shalanee; Gibson, John P.; Gondro, Cedric; Okeyo Mwai, Ally; Ojango, Julie M.K.; Rao, E.J.O.; Dessie, Tadelle; Mujibi, Denis; Rege, J.E.O. (2018)
Genetic diversity of the indigenous cattle of Kenya, Uganda, Ethiopia and Tanzania using high-density SNP data. The indigenous cattle make a significant contribution to the livelihood of many communities in Ethiopia, Tanzania and other countries in eastern Africa. Here, we identify the genetic structure and the admixture levels of several East African indigenous cattle breeds in Ethiopia and Tanzania. Two ‘groups’ were studied: Indigenous cattle consisting of a number of breeds; and Mpwapwa cattle – a composite breed. A total of 386 individual animals from the two groups were genotyped using the Illumina high-density Bovine SNP chip (778k Panel). Principal component analysis was used to study the genetic structure and admixture levels of the indigenous cattle, and Mpwapwa were estimated using the ADMIXTURE program. All East African indigenous breeds other than the Ankole appear genetically closely related to each other and consist of a mixture of African taurine and indicine signals. Ethiopian indigenous breeds, Fogera, Danakil Harar and Ethiopian Boran show high purity, whereas Ethiopian Central Highland Breed and the Begait samples show significant amounts of European Bos taurus admixture. Tanzanian indigenous cattle, Singida White and Iringa Red, have a high degree of purity while the TALIRI Boran shows some European Bos taurus genetic background. The synthetic Mpwapwa breed had estimated breed proportions of Bos indicus, African Bos taurus and European Bos taurus of 0.82, 0.05 and 0.13 respectively. These results are useful for genetic conservation and genetic improvement programs.